MOTIF DAN KEPUASAN PENGGUNA NETFLIX SEBAGAI MEDIA STREAMING DI KALANGAN REMAJA KOTA DENPASAR - Artika Sari, Ni Putu Pradnya; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium; Vol 2 No 2 (2021): Jurnal Ilmu Komunikasi Vol 2 No 2 Tahun 2021, 2021)
Netflix known as entertainment company specializing in streaming service that allows their members to watch TV shows or movies on an internet-connected device without commercials. Netflix can be use on internet-connected devices that offer the Netflix app, such as tablets, smart TV and smartphone. The purpose of this research are to find the motives and the satisfactions of youth in Denpasar by using Netflix as a streaming service. This study using Uses and Gratification Theory by Dennis McQuail. This research uses descriptive quantitative method with purposive sampling technique. Data obtained by distributing questionnaire. The result shows there are two of the four motives that could be satisfied are information motive and integration and social interaction motive. Besides that, motive that has not been able to satisfied are personal identity motive and entertainment motive. Keyword: Motive, Satisfication, Youth, Netflix